Efficacy and safety of minimally invasive surgery with thrombolysis in intracerebral haemorrhage evacuation (MISTIE III): a randomised, controlled, open-label, blinded endpoint phase 3 trial - Hanley, Daniel F.; Unterberg, Andreas (The lancet, 2019)
Background - Acute stroke due to supratentorial intracerebral haemorrhage is associated with high morbidity and mortality. Open craniotomy haematoma evacuation has not been found to have any benefit in large randomised trials. We assessed whether minimally invasive catheter evacuation followed by thrombolysis (MISTIE), with the aim of decreasing clot size to 15 mL or less, would improve functional outcome in patients with intracerebral haemorrhage. - Methods - MISTIE III was an open-label, blinded endpoint, phase 3 trial done at 78 hospitals in the USA, Canada, Europe, Australia, and Asia. We enrolled patients aged 18 years or older with spontaneous, non-traumatic, supratentorial intracerebral haemorrhage of 30 mL or more. We used a computer-generated number sequence with a block size of four or six to centrally randomise patients to image-guided MISTIE treatment (1·0 mg alteplase every 8 h for up to nine doses) or standard medical care. Primary outcome was good functional outcome, defined as the proportion of patients who achieved a modified Rankin Scale (mRS) score of 0-3 at 365 days, adjusted for group differences in prespecified baseline covariates (stability intracerebral haemorrhage size, age, Glasgow Coma Scale, stability intraventricular haemorrhage size, and clot location). Analysis of the primary efficacy outcome was done in the modified intention-to-treat (mITT) population, which included all eligible, randomly assigned patients who were exposed to treatment. All randomly assigned patients were included in the safety analysis. This study is registered with ClinicalTrials.gov, number NCT01827046. - Findings - Between Dec 30, 2013, and Aug 15, 2017, 506 patients were randomly allocated: 255 (50%) to the MISTIE group and 251 (50%) to standard medical care. 499 patients (n=250 in the MISTIE group; n=249 in the standard medical care group) received treatment and were included in the mITT analysis set. The mITT primary adjusted efficacy analysis estimated that 45% of patients in the MISTIE group and 41% patients in the standard medical care group had achieved an mRS score of 0-3 at 365 days (adjusted risk difference 4% [95% CI −4 to 12]; p=0·33). Sensitivity analyses of 365-day mRS using generalised ordered logistic regression models adjusted for baseline variables showed that the estimated odds ratios comparing MISTIE with standard medical care for mRS scores higher than 5 versus 5 or less, higher than 4 versus 4 or less, higher than 3 versus 3 or less, and higher than 2 versus 2 or less were 0·60 (p=0·03), 0·84 (p=0·42), 0·87 (p=0·49), and 0·82 (p=0·44), respectively. At 7 days, two (1%) of 255 patients in the MISTIE group and ten (4%) of 251 patients in the standard medical care group had died (p=0·02) and at 30 days, 24 (9%) patients in the MISTIE group and 37 (15%) patients in the standard medical care group had died (p=0·07). The number of patients with symptomatic bleeding and brain bacterial infections was similar between the MISTIE and standard medical care groups (six [2%] of 255 patients vs three [1%] of 251 patients; p=0·33 for symptomatic bleeding; two [1%] of 255 patients vs 0 [0%] of 251 patients; p=0·16 for brain bacterial infections). At 30 days, 76 (30%) of 255 patients in the MISTIE group and 84 (33%) of 251 patients in the standard medical care group had one or more serious adverse event, and the difference in number of serious adverse events between the groups was statistically significant (p=0·012). - Interpretation - For moderate to large intracerebral haemorrhage, MISTIE did not improve the proportion of patients who achieved a good response 365 days after intracerebral haemorrhage. The procedure was safely adopted by our sample of surgeons. - Funding - National Institute of Neurological Disorders and Stroke and Genentech.